1999
DOI: 10.1161/01.atv.19.3.700
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between the G20210A Mutation of the Prothrombin Gene and Oral Contraceptive Use in Deep Vein Thrombosis

Abstract: Abstract-Single-point mutations in the gene coding for prothrombin (factor II:A20210) or factor V (factor V:A1691) are associated with an increased risk of venous thromboembolism. The use of oral contraceptives is also a strong and independent risk factor for the disease, and the interaction between factor V:A1691 and oral contraceptives greatly increases the risk. No information is available about the interaction between oral contraceptives and mutant prothrombin. We investigated 148 women with a first, objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
126
0
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(135 citation statements)
references
References 33 publications
5
126
0
4
Order By: Relevance
“…7 A markedly increased risk of VTE was also seen in oral contraceptive users with concomitant protein C, protein S and antithrombin deficiencies or carriership of the prothrombin G20210A mutation. 8 In postmenopausal women with factor V Leiden who used hormone replacement therapy Rosendaal et al 9 found a 15-fold increased risk of venous thrombosis. Although these genetic and environmental risk factors interact with each other with a multiplicative effect, the molecular mechanism of the interaction is still unknown.…”
Section: Aggravation Of Clinical Phenotypementioning
confidence: 99%
“…7 A markedly increased risk of VTE was also seen in oral contraceptive users with concomitant protein C, protein S and antithrombin deficiencies or carriership of the prothrombin G20210A mutation. 8 In postmenopausal women with factor V Leiden who used hormone replacement therapy Rosendaal et al 9 found a 15-fold increased risk of venous thrombosis. Although these genetic and environmental risk factors interact with each other with a multiplicative effect, the molecular mechanism of the interaction is still unknown.…”
Section: Aggravation Of Clinical Phenotypementioning
confidence: 99%
“…15,[22][23][24] Whereas the beneficial effects of thirdgeneration progestins on the levels of high-density lipoprotein cholesterol had suggested that they might lower the risk of arterial thrombosis, studies demonstrated a relative risk of venous thrombosis in users of these oral contraceptives that was six to nine times that in nonusers. [22][23][24] Of 16 original studies addressing the risk of thirdgeneration as compared with second-generation oral contraceptives, 3 found no difference between the two types of contraceptives [25][26][27] and all the others found higher risks associated with the use of third-generation preparations, with estimates of risk ranging from 1.4 to 4 times as high as that associated with secondgeneration preparations. 15,[21][22][23][24][28][29][30][31][32][33][34][35] In a prospective study involving a pharmacy data base in the Netherlands, the absolute risk associated with third-generation contraceptives approached 1 per 1000 new users per year during the first year of use.…”
Section: The Effect Of Progestins In Combined Preparationsmentioning
confidence: 99%
“…[57][58][59] Another recently identified genetic defect, a mutation in the prothrombin gene (the substitution of adenine for guanine at nucleotide 20210), is a moderate risk factor for thrombosis; its prevalence among white persons is approximately 2 to 4 percent, 60,61 and it has also been shown to increase the risk of venous thrombosis associated with the use of oral contraceptives. 27 Women who have a prothrombotic defect have oral-contraceptive-associated venous thrombosis not only more often, but also sooner: their risk of venous thrombosis in the first year of use is more than 10 times that in later years. 62 Thus, the development of venous thrombosis in the first year of use may be a warning that a woman has a hereditary risk factor for venous thrombosis.…”
Section: Other Hereditary Prothrombotic Defectsmentioning
confidence: 99%
“…1 Carriership of the 20210A allele is associated with a slight increase in the risk of recurrent VTE, 6 and the presence of other VTE risk factors increases the risk of VTE in 20210A carriers. [7][8][9][10][11] Polymorphisms in the anticoagulant pathways may also modify the VTE risk in 20210A carriers. The endothelial protein C receptor (EPCR) enhances the rate of protein C activation, thus contributing to the regulation of thrombin formation by the protein C anticoagulant pathway.…”
Section: Introductionmentioning
confidence: 99%